WRITING A HISTORY OF RESEARCH INSTITUTE AND COMMUNITY SERVICE UNESA: STRENGTHENING THE COUNTRY THROUGH RESEARCH AND COMMUNITY SERVICE - R.N. Bayu Aji; Arifah Kaharima; Ms Kisyani (Universitas Negeri Surabaya, 2022)
The State University of Surabaya (Unesa) as a leading university in Indonesia, always contributes to building the country through the tridharma of higher education, namely education, research and community service. Unesa's research and community service (PKM) footprint has now reached the age of 58 years. Therefore, these steps must be well documented through historical narratives, so that LPPM Unesa in the future remains a sustainable institution without having to forget its historical roots. Writing the history of the Unesa Research and Community Service Institute (LPPM) will pass through 4 important periods. First, the period when Unesa was still an IKIP. Second, the wider mandate period in which Unesa will spread its wings and this will definitely affect the strategic policy direction of LPPM Unesa. Third, when Unesa was in the form of a Public Service Agency (BLU). Fourth, is Unesa towards a Legal Entity State University (PTNBH). Through this history book, the gold ink of LPPM Unesa in the process of building the country through research and community service in Indonesia for a better life of the nation will be documented.